Eficiência da produção de sementes de soja na COTRIPAL - Panambi - Muller, Ronaldo Ernesto (2011)
The present study aimed to analyze the efficiency of production, processing and marketing of soybean seeds at COTRIPAL AGROPECUÁRIA COOPERATIVA, the unit of Vila Arco Íris, in the city of Panambi, RS, from the period between the harvests of 2004/2005 to 2008/2009. For this we analyzed the historical data and information regarding the area inscribed, approved area, prediction of reception, quantity received, benefit amount, amount approved, amount traded within and outside the state and the percentage of participation of companies in the seed companies produced and marketed. The results show low efficiency in the percentage of approval of the area inscribed, with a mean period of 74.69% of the approved area. The efficiency of the reception obtained an average result of 62.75% and the improvement in the average yield was 57.14%. For the seed examined by the laboratory, the approval was 96.08%. And relating to the marketing the average of the period analyzed was 75.42% and the sales volume, 95.16% was sold within the state of Rio Grande do Sul. In relation to the percentage of ownership of companies in production and marketing of seeds, it is observed in the 2008/2009 harvest, a major division of the market with the entry of other companies. There is a need to improve efficiency in the production of soybeans, with the development of procedures for prediction of cultivars with higher demand in the next harvest and adoption of appropriate production techniques.